1994
DOI: 10.1002/art.1780370612
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ICAM‐R (ICAM‐3), a novel counter‐receptor for LFA‐1, in rheumatoid and nonrheumatoid synovium

Abstract: Objective. To study the distribution of intercellular adhesion molecule receptor (ICAM-R, or ICAM3), a novel ligand for the leukointegrin lymphocyte function-associated antigen 1 (LFA-l), in normal and rheumatoid synovial membranes and to compare this with the distribution of ICAM-1, ICAM-2, vascular cell adhesion molecule 1 (VCAM-l), and endothelial leukocyte adhesion molecule 1 (ELAM-1).Methods. We performed immunohistochemical analyses of frozen sections of normal and rheumatoid synovial tissue using monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Cytospin preparations yielded immunohistochemical results in accordance with data obtained from cryosections: ICAM-1 was expressed within the enlarged synovial intima, the subsynovial region and the intima of blood vessels, whereas its expression in lymphocytic aggregates and follicles was low (with the exception of the follicular dendritic cells). Our findings are well in line with the results of others who have demonstrated a high expression of ICAM-1 on macrophage-like synovial cells and endothelial cells [6,7,9] and a paucity of ICAM-1 expression in lymphocyte-rich areas [9,25]. Some authors have also demonstrated expression of ICAM-1 on a high percentage of synovial fibroblasts cultured in vitro [6].…”
Section: Icam-1 Expression On Cells Isolated From Rssupporting
confidence: 81%
See 1 more Smart Citation
“…Cytospin preparations yielded immunohistochemical results in accordance with data obtained from cryosections: ICAM-1 was expressed within the enlarged synovial intima, the subsynovial region and the intima of blood vessels, whereas its expression in lymphocytic aggregates and follicles was low (with the exception of the follicular dendritic cells). Our findings are well in line with the results of others who have demonstrated a high expression of ICAM-1 on macrophage-like synovial cells and endothelial cells [6,7,9] and a paucity of ICAM-1 expression in lymphocyte-rich areas [9,25]. Some authors have also demonstrated expression of ICAM-1 on a high percentage of synovial fibroblasts cultured in vitro [6].…”
Section: Icam-1 Expression On Cells Isolated From Rssupporting
confidence: 81%
“…ICAM-1 (intercellular adhesion molecule-1 or CD54), which is an important adhesion molecule in inflammation [2,3], is thought to play a central role in this autoimmune process [4,5]. In several studies the tissue distribution, serum level and synovial fluid (SF) level of soluble ICAM-1 (sICAM-1) have been characterized in RA patients [6][7][8][9][10][11][12][13][14], but it is still unclear (a) which of the RS cells comprise the main source of sICAM-1 and (b) whether the elevated sICAM-1 levels seen in SF and serum originate in the RS. To our mind, an adequate approach to solving these problems is provided only by analysis of the sICAM-1-shedding capacity of RS.…”
Section: Introductionmentioning
confidence: 99%
“…This has indirectly implicated that the major endothelial ligands of these lymphocyte homing receptors (ICAM-1 or -2, VCAM-1, PNAd, and hyaluronate, respectively) may play a role in synovial adhesion. Indeed, blood vessels in heterogeneous materials of inflamed synovia have been shown to express VCAM-1, PNAd, E-and P-selectin, and ICAMs (16,17,(19)(20)(21)(22). This study is the first systematic effort to analyze the expression of all known endothelial adhesion molecules simultaneously in one series of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…One of these sections was stained with hematoxylin and eosin (H&E) in order to properly orient the remainder of the sections. An avidin-biotin complex (ABC) method was used as previously described (24) and as detailed in previous immunohistochemical studies (18). As an antibody control, mouse plasma was substituted for the primary monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%